IMPROVING NARRATIVE WRITING SKILLS THROUGH THE APPLICATION OF THE MIND MAP METHOD IN GRADE IV STUDENTS AT SDN 39 PONTIANAK - Fitri Jayanti (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This study aims to be able to see and find out how to improve students' writing skills after using the mind mapping method and besides that to find out students' abilities in writing narrative essays using the mind mapping method in fourth grade students at SDN 39 Pontianak city . This type of research is classroom action research (CAR) using a psychological approach. In this study two cycles were carried out, each cycle was carried out 3 times face to face, by going through the stages of Planning, Implementation, Observation, and Reflection. The subjects of this study were fourth grade students at SDN 39 Pontianak City, totaling 27 students consisting of 10 male students and 17 female students. The data sources used in this study were obtained directly from students and teachers at the school where the research took place. In this research data collection was carried out using tests, and documentation and observation. Data analysis used is qualitative data analysis. The final results of this study prove that the lesson of writing narrative essays has increased, this can be seen from the results of the average score from cycle I to cycle II in cycle II, the level of students' writing skills has increased to 100% pass and there is no score below the KKM. Besides that, using mind maps can increase student self-confidence and students' creative sense in class.